Clinical utility of a biopsy-based cell cycle gene expression assay in localized prostate cancer. (April 2014) - Shore, Neal; Concepcion, Raoul; Saltzstein, Daniel; Lucia, M. Scott; van Breda, Arletta; Welbourn, William; Lewine, Nicolas; Gustavsen, Gary; Pothier, Kristin; Brawer, Michael K.
Abstract Objective: The CCP signature test (Prolaris) quantifies a patient's risk of disease progression and prostate cancer specific mortality using a gene-expression-based cell cycle progression (CCP) score. This study evaluated the potential clinical utility of the CCP test in a US-based clinical setting. Methods: Urologists who participated in a prospective clinical study were sent a retrospective questionnaire to assess the value of the CCP test result. Fifteen board-certified urologists participated in the study, representing 15 distinct community urology group practices. Questionnaires were received for 294 evaluable patients. All patients had localized prostate cancer (T1–T3b, N0, M0). Results: Physicians found the CCP score valuable and indicated that 55% of tests generated a mortality risk that was either higher or lower than expected. Physicians also indicated that 32% of test results would lead to a definite or possible change in treatment. The data suggest that the test would have the net effect of shifting patients from more aggressive treatment to more conservative treatment. This was evidenced by the significant association between change in treatment and lower CCP scores (p < 0.002) and by the fact that 62% of tests likely to lead to a definite or possible change in treatment had mortality risks lower than the physician expected versus only 10% with risks higher than expected. Study limitations: This study measured the retrospectively assessed likelihood of change in treatment as estimated by the physician, not the actual change in treatment. Conclusions: The CCP score adds meaningful new information to risk assessment for localized prostate cancer patients. Real-world use of the test is likely to lead to a change in treatment in a significant portion of tested patients, particularly by shifting patients towards more conservative management. This could reduce overtreatment of patients with less aggressive disease, decreasing patient morbidity and costs for payers and the healthcare system.